STRATEGI COPYWRITING PADA IKLAN TIKTOK: ANALISIS KUALITATIF ATAS DAYA TARIK PESAN DI MEDIA VIDEO PENDEK - Tresnawati, Yuni; Nasution, Sri Mulyati Sari; Hermawan, Yhesa (Reputasi : Jurnal Public Relations, 2026)
The rapid development of the TikTok platform has transformed how brands build marketing communication in the digital environment. With its short-video format, advertising messages must be concise, clear, and engaging within a very limited time. Copywriting plays a crucial role in determining whether audiences stay, interact, or take further action. This study aims to analyze the application of copywriting techniques in TikTok advertisements and identify patterns that contribute to message effectiveness, supported by the AIDA model as a persuasive communication framework. This research employed a descriptive qualitative approach by observing 15 TikTok advertisements from beauty, culinary, education, digital applications, and service categories. Data were collected through video observation, caption documentation, audience responses, and narrative transcription, then analyzed using thematic analysis. The results show that effective TikTok copywriting is influenced by strong opening hooks, relevant mini storytelling, casual language styles, and explicit calls to action. These findings emphasize the importance of adapting persuasive communication strategies to the characteristics of short-video platforms and provide practical insights for brands in optimizing TikTok advertising content.